INFLUENCE OF WORK ENVIRONMENT AND EMPLOYEE MOTIVATION ON EMPLOYEE RETENTION AT SILOAM HOSPITAL MANADO - Rattu, Rhacyella R.; Tielung, Maria V.J (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: Employee retention is an effort to retain employees in the organization. It refers to policies and practices that direct employees to survive in an organization for a longer period of time. Higher employee retention will affect the organization's performance in achieving the goals and mission of the organization. According to that, this research is analyzing the influence of Work Environment and Employee Motivation on Employee Retention in Siloam Hospital Manado. The samples of this research are 100 employees from 311 employees at Siloam Hospital and to analyse the sample in this research is using multiple regressions with the IBM SPSS Statistics.Â Based on the result of hypothesis work environment and employee motivation has a positive and significant influence on employee retention. This model applies in health organization which is Siloam Hospital Manado. Siloam Hospital Manado should improve the work environment and increase the employee motivation so the organization can retain the loyal employee. Siloam Hospital Manado should pay more attention to employee retention because the higher employee retention will affect the organizationâ€™s performance in achieving the goals and mission of the organization.Â Keywords: work environment, employee motivation, employee retention